Immune changes in hilar tumor draining lymph nodes following node sparing neoadjuvant chemoradiotherapy of localized cN0 non-small cell lung cancer - Khalifa, Jonathan; Thébault, Noémie; Scarlata, Clara-Maria; Norkowski, Emma; Massabeau, Carole; Brouchet, Laurent; Peries Bataille, Sophie; Casaroli, Christelle; Vaz, Liza; Valle, Carine; Sarot, Emeline; Saint-Laurent, Nathalie; et al. (Frontiers in Oncology, 2023)
Background: While much progress has been accomplished in the understanding of radiation-induced immune effects in tumors, little is known regarding the mechanisms involved at the tumor draining lymph node (TDLN) level. The objective of this retrospective study was to assess the immune and biological changes arising in non-involved TDLNs upon node sparing concurrent chemoradiotherapy (CRT) of non-small cell lung cancer (NSCLC) tumors. Methods: Patients with proven localized (cN0M0) NSCLC, treated by radical surgery plus lymph node dissection with (CRT+) or without (CRT-) neoadjuvant chemoradiotherapy, whereby radiotherapy was targeted on the primary tumor with no significant incidental irradiation of the non-involved TDLN station (stations XI), were identified. Bulk RNA sequencing of TDLNs was performed and data were analyzed based on differential gene expression (DGE) and gene sets enrichment. Results: Sixteen patients were included and 25 TDLNs were analyzed: 6 patients in the CRT+ group (12 samples) and 10 patients in the CRT- group (13 samples). Overall, 1001 genes were differentially expressed between the two groups (CRT+ and CRT-). Analysis with g-profiler revealed that gene sets associated with antitumor immune response, inflammatory response, hypoxia, angiogenesis, epithelial mesenchymal transition and extra-cellular matrix remodeling were enriched in the CRT+ group, whereas only gene sets associated with B cells and B-cell receptor signaling were enriched in the CRT- group. Unsupervised dimensionality reduction identified two clusters of TDLNs from CRT+ patients, of which one cluster (cluster 1) exhibited higher expression of pathways identified as enriched in the overall CRT+ group in comparison to the CRT- group. In CRT+ cluster 1, 3 out of 3 patients had pathological complete response (pCR) or major pathological response (MPR) to neoadjuvant CRT, whereas only 1 out of 3 patients in the other CRT+ cluster (cluster 2) experienced MPR and none exhibited pCR. Conclusion: Neoadjuvant node sparing concurrent CRT of NSCLC patients is associated with distinct microenvironment and immunological patterns in non-involved TDLNs as compared to non-involved TDLNs from patients with non-irradiated tumors. Our data are in line with studies showing superiority of lymph node sparing irradiation of the primary tumor in the induction of antitumor immunity.